2017
DOI: 10.1021/acscatal.7b00254
|View full text |Cite
|
Sign up to set email alerts
|

Combining Rh-Catalyzed Diazocoupling and Enzymatic Reduction To Efficiently Synthesize Enantioenriched 2-Substituted Succinate Derivatives

Abstract: We report the development of a modular, one-pot, sequential chemoenzymatic system for the formal enantioselective construction of the C–C bond in 2-aryl 1,4-dicarbonyl compounds. This sequence comprises a rhodium-catalyzed diazocoupling that provides >9:1 selectivity for heterocoupling of two diazoesters and a reduction mediated by an ene-reductase (ER), which occurs in up to 99% enantiomeric excess (ee). The high yield and enantioselectivity of this system result from the preferential generation of an (E)-alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 48 publications
4
33
0
Order By: Relevance
“…Steric and electronic perturbation of the aryl diazoacetate coupling partner (R1 and R2) were well tolerated, and both ethyl diazoesters and amides could be used (R3). With the exception of the previously unreported amide substrate, these substrates are in line with the known scope for dirhodium catalyzed diazo coupling, 23,25 indicating that the ArM enables the desired dirhodium activity while significantly reducing undesired side reactions such as water O-H insertion.…”
Section: Arm Directed Evolutionsupporting
confidence: 59%
See 3 more Smart Citations
“…Steric and electronic perturbation of the aryl diazoacetate coupling partner (R1 and R2) were well tolerated, and both ethyl diazoesters and amides could be used (R3). With the exception of the previously unreported amide substrate, these substrates are in line with the known scope for dirhodium catalyzed diazo coupling, 23,25 indicating that the ArM enables the desired dirhodium activity while significantly reducing undesired side reactions such as water O-H insertion.…”
Section: Arm Directed Evolutionsupporting
confidence: 59%
“…Finally, THF and dioxane were found to be suitable co-solvents for the diazo coupling reaction. In all cases, the observed selectivity is substantially lower than that typically observed for the analogous reaction in organic solvent under cryogenic conditions (>10/1) 23 , so improving this was a key goal of directed evolution. A significant amount (39%) of the donor-acceptor diazo substrate reacted with water, forming OH insertion product 6, so minimizing this side reaction would also be required as in our previous evolution efforts 18,19 .…”
Section: Arm Directed Evolutionmentioning
confidence: 89%
See 2 more Smart Citations
“…A subsequent study from the same laboratories reported a related system for the cooperative synthesis of styrenyl epoxides 29 . More recently, these groups have disclosed a chemoenzymatic synthesis of 2-aryl-succinate derivatives using a Rh-catalyzed diazocoupling-enereductase sequential reaction manifold 30 .…”
mentioning
confidence: 99%